Validation of immune-complex enzyme immunoassays for diagnosis of pneumococcal pneumonia among adults in Kenya. - Scott, J; Hall, A; Leinonen, M (2000)
The efficacy of pneumococcal vaccines in protecting against pneumococcal pneumonia can feasibly be measured only with a diagnostic technique that has a high specificity (0.98 to 1.00) and a sensitivity greatly exceeding that of blood cultures (>0.2 to 0.3). In this context immune-complex enzyme immunoassays (EIAs) offer a novel, convenient diagnostic method, and we have investigated three such assays with appropriate study populations in Kenya. Sera from 129 Kenyan adults with pneumococcal pneumonia and 97 ill controls from the same clinics, but without pneumococcal disease syndromes, were assayed with immune-complex EIAs for pneumolysin, C-polysaccharide, and mixed capsular polysaccharides (Pneumovax II). At an optical density (OD) threshold yielding a specificity of 0.95, the sensitivities (95% confidence intervals) of the assays were 0.22 (0.15 to 0.30), 0.26 (0.19 to 0.34), and 0.22 (0.15 to 0.29), respectively. For pneumolysin immune complexes, human immunodeficiency virus (HIV)-positive patients had a higher mean OD than HIV-negative patients (639 versus 321; P < 0.0001), but stratification by HIV infection status did not alter the performance of this test. Combining the results of all three EIAs did not enhance the diagnostic performances of the individual assays. In Kenyan adults the sensitivities of the immune-complex EIAs could exceed that of blood cultures only at levels of specificity that were insufficient for the performance of vaccine efficacy studies.